Analysis of Risk Factors for Dengue Virus Infection with Warning Signs in Child Care at Haji Hospital Makassar City for the 2022-2023 Period - Nur, A. Ahmad Fitrah Ramadhan; Maddeppungeng, Martira; Maulani, Destya; Ganda, Idham Jaya; Darussalam, Andi Husni Esa (Formosa Journal of Science and Technology, 2024)
Dengue Hemorrhagic Fever ranked among the top 10 diseases with 193 cases in the Inpatient Hospital of Haji Hospital, Makassar City in 2018. The WHO's Dengue Virus Infection (IVD) classification with 7 Warning Signs helps identify severe IVD risks in both pediatric and adult patients. A retrospective cohort study analyzed 132 medical records of pediatric patients aged 4 months to 18 years using Purposive Sampling. Most IVD patients were aged 5-18 years (72.8%), male (56.1%), had good nutritional status (69.7%), and experienced fever for <4 days before treatment (58.3%). Significant risk factors for IVD with Warning Signs included gender (p-value 0.029) and nutritional status (p-value 0.025), while age (p-value 0.914) and duration of fever (p-value 0.323) were not significant. Gender and nutritional status are significant risk factors for IVD with Warning Signs.